DFT study on type-II photocatalyst for overall water splitting: g-GaN/C2N van der Waals heterostructure. (19th April 2023) - Huang, Xin; Shu, Xiaomei; Li, Jie; Cui, Zhongguo; Cao, Shengzhe; Chen, Wei; Yin, Jie; Yan, Gang; Zhao, Huaihong; Hu, Jing; Yang, Zhihong; Wang, Yunhui
Abstracts: Constructing van der Waals heterostructure has triggered enormous interest in the field of photocatalytic water splitting. Herein, we have investigated the structural, electronic and optical properties of g-GaN/C2 N heterostructure by first-principles methods, and further discussed the implications from the viewpoint of photocatalytic applications. Our results show that g-GaN/C2 N heterostructure is a type-II heterostructure, possessing staggered energy band arrangements, which benefits to the effective spatial-separation of photogenerated carriers. The bandgap is predicted to be 1.92 eV, governing a wide optical absorption spectrum from visible-light to ultraviolet-light with the magnitude of 10 5 cm −1 . Moreover, its band edges span water redox potentials, satisfying the requirement of overall photocatalytic water splitting. In addition, the electronic properties of g-GaN/C2 N heterostructure could be modulated by applying biaxal strain, resulting in an increasement of optical absorptions in the visible-light range. Finally, excellent stability of adsorbing water molecule on the g-GaN/C2 N heterostructure is shown. These theoretical predictions suggest that the g-GaN/C2 N heterostructure is promising for photocatalytic water splitting. Graphical abstract: Image 1 Highlights: A type-II g-GaN/C2 N heterostructure is designed for photocatalytic water splitting. Strain can modulate the electronic and optical properties effectively. Excellent stability of adsorbing water molecule on the g-GaN/C2 N heterostructure.